A novel equivalent-circuit model and parameter identification method for supercapacitor performance. (July 2018) - Xu, Dan; Zhang, Le; Wang, Bin; Ma, Guangliang
Abstract: To accurately describe the operating mechanism of supercapacitor (SC), a precise model should be established for the SC. In this paper, an equivalent-circuit model with a controlled current source is proposed, which can simulate the dynamic behavior of the SC. The recursive least square algorithm with forgetting factor is introduced to identify model parameters. Experimental and simulation results are presented to verify the proposed equivalent-circuit model. Results show a very good performance since the maximum relative modeling error do not exceed 1%. Therefore, the proposed model with its parameter identification method can effectively reveal the operating mechanism of the SC.